Knowledge and Antibiotic Adherence in Acute Respiratory Infection Patients at Karang Intan 1 Clinic - Aprianti , Safrina; Wati, Helmina; Dharmayati, Evy (Universitas Muhammadiyah Surabaya, 2025)
Acute Respiratory Infection (ARI) is a bacterial infection affecting the respiratory tract, from the nasal cavity to the lungs, and contributes to nearly 4 million deaths globally each year. Knowledge refers to the information acquired and retained by individuals, while compliance indicates the extent to which patients adhere to medication instructions provided by healthcare professionals. This study aimed to assess the level of knowledge regarding antibiotics and patients’ compliance with antibiotic use. A prospective observational quantitative approach was employed from January to April 2025 at the Karang Intan 1 Health Center. The study used a cross-sectional design and included 80 ARI patients selected through total sampling. Data were collected using structured questionnaires over a two-month period. Results showed that the most frequently used antibiotic was cefadroxil, a first-generation cephalosporin, used by 52 respondents (65%). The knowledge assessment revealed that 76 respondents (95%) had good knowledge, while 4 respondents (5%) had poor knowledge. In terms of compliance, 65 respondents (81.25%) were compliant, 10 respondents (12.5%) were fairly compliant, and 5 respondents (6.25%) were less compliant. Statistical analysis using the Chi-square test demonstrated a significant relationship between knowledge level and antibiotic compliance (p < 0.000). This indicates that higher knowledge levels are associated with better compliance in antibiotic use among ARI patients at Karang Intan 1 Health Center